2010
DOI: 10.3928/1081597x-20100921-12
|View full text |Cite
|
Sign up to set email alerts
|

Technical Aspects of the WaveLight FS200 Femtosecond Laser

Abstract: The WaveLight FS200 femtosecond laser provides a high reproducibility for cutting three-dimensional tissue structures. The IOP increase is comparable to other microkeratomes and femtosecond lasers. The minimized opaque bubble layers allow the surgeon to perform an excimer laser treatment immediately after FS200 flap creation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Mrochen et al 16 report that the technical features of the Wavelight FS200, such as optical design, pulse energy, and scanning algorithms at a high repetition rate, allow high reproducibility for tissue cutting, with an SD of less than 10 mm in depth and 0.1 mm laterally. The authors found that the intraocular pressure (IOP) increases up to 150 mm Hg during applanation.…”
Section: Discussionmentioning
confidence: 98%
“…Mrochen et al 16 report that the technical features of the Wavelight FS200, such as optical design, pulse energy, and scanning algorithms at a high repetition rate, allow high reproducibility for tissue cutting, with an SD of less than 10 mm in depth and 0.1 mm laterally. The authors found that the intraocular pressure (IOP) increases up to 150 mm Hg during applanation.…”
Section: Discussionmentioning
confidence: 98%
“…The creation of a flap thickness ranging from 100 to 130 μm with a standard deviation of 10–15 μm using femtosecond lasers is considered state of the art 2,3,7. Femtosecond laser surgery offers a safety advantage over microkeratome-based LASIK procedures 814.…”
Section: Introductionmentioning
confidence: 99%
“…WaveLight FS200 femtosecond laser system is a low-energy and high pulse frequency laser that emits laser pulses with duration of 350 fs at a wavelength of 1,050 nm and pulse repetition rate of 200 kHz 7. IntraLase 60 kHz system uses a flat contact surface, while WaveLight FS200 uses a curved contact surface 3,7…”
Section: Introductionmentioning
confidence: 99%
“…According to the manufacturers, the WaveLight platform provides flaps with repeatable thickness, sharp cutting edges and smooth stromal beds. A recent in vitro study in porcine eyes demonstrated the capability of the WaveLight platform to create flaps with repeatable thickness18; another study with light and electron microscopy revealed that this platform produces smooth surfaces 19…”
Section: Discussionmentioning
confidence: 99%